Analysis of E-Government Implementation in Semarang City Based on Mayor Decree No.50/571 of 2023 on SPBE Architecture Determination - Eka Ardhianto; Siti Sholihah Ari Susanti; Heribertus Yulianton; Widiyanto Tri Handoko; Kristiawan Nugroho (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
This study provides an in-depth analysis of the implementation of e-government in Semarang City, driven by Mayor Decree No.50/571 of 2023 concerning the establishment of the Electronic-Based Government System (SPBE) framework. The research evaluates the alignment of Semarang City's e-government strategies with national regulations, including PerPres No.95/2018 on SPBE, PermenPANRB No.5/2018 on SPBE evaluation criteria, and PerPres No.132/2022 on national SPBE architecture. Employing qualitative methods through literature reviews, interviews, surveys, and observations, this study examines e-government readiness, smart governance, digital service integration, and benchmarking practices. The results highlight significant progress in enhancing public service efficiency and transparency, though challenges such as system interoperability, cybersecurity risks, and public engagement remain. Recommendations include strengthening infrastructure, improving human resource capacity, and fostering citizen involvement for sustainable e-government development.